2020
DOI: 10.1038/s41397-020-0161-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gene modules associated with survival of diffuse large B-cell lymphoma treated with CHOP-based chemotherapy

Abstract: Diffuse Large B-cell Lymphoma (DLBCL), a heterogeneous disease, is influenced by complex network of gene interactions. Most previous studies focused on individual genes, but ignored the importance of intergenic correlations. In current study, we aimed to explore the association between gene networks and overall survival (OS) of DLBCL patients treated with CHOP-based chemotherapy (cyclophosphamide combination with doxorubicin, vincristine and prednisone). Weighted gene co-expression network analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
7
0
1
Order By: Relevance
“…36 A systematic study of diffuse large B-cell lymphoma has shown that LCP2 is a prognostic marker and its high expression is associated with good survival. [37][38][39] These results confirmed that the functional module identified in our study has important significance in hematological tumors.…”
Section: Discussionsupporting
confidence: 88%
“…36 A systematic study of diffuse large B-cell lymphoma has shown that LCP2 is a prognostic marker and its high expression is associated with good survival. [37][38][39] These results confirmed that the functional module identified in our study has important significance in hematological tumors.…”
Section: Discussionsupporting
confidence: 88%
“…CD3D, CLU, ICOS, KLRB1 and LAT appear to be prognostic factors in a range of malignancies, such as B-NHL, 19 , 20 colorectal cancer, 21 , 22 ovarian cancer, 23 bladder cancer, 24 breast cancer, 25 , 26 cervical cancer, 27 and lung cancer, 28–31 and play important roles in lymphoma development. 32–36 Of note, the role and prognostic value of CHN1 in B-NHL have never been reported before, so we focused our attention on CHN1 in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan-Meier curves showed that the high expression of these genes was correlated with a prolonged survival time in both GSE10846 (Figure 3A-F, p < 0.05) and GSE117556 (Figure 3G-L, p < 0.05). CD3D, CLU, ICOS, KLRB1 and LAT appear to be prognostic factors in a range of malignancies, such as B-NHL, 19,20 colorectal cancer, 21,22 ovarian cancer, 23 bladder cancer, 24 breast cancer, 25,26 cervical cancer, 27 and lung cancer, [28][29][30][31] and play important roles in lymphoma development. [32][33][34][35][36] Of note, the role and prognostic value of CHN1 in B-NHL have never been reported before, so we focused our attention on CHN1 in this study.…”
Section: Identification and Validation Of 6 Genes Related To Survival In Dlbcl Patientsmentioning
confidence: 99%
“…Another candidate is the NT5C2 gene, which is known to confer treatment resistance against thiorubin in acute lymphocytic leukemias [41]. For ANXA7 it was shown that resistance in different cancer types has been observed [43,44].…”
Section: Prediction Of Regulatory Regions That Mediate Chemoresistance In Rpe-1 Cellsmentioning
confidence: 99%